PENGARUH FINANCING TO DEPOSIT RATIO DAN CAPITAL ADEQUACY RATIO TERHADAP RETURN ON ASSET DENGAN NON PERFORMING FINANCING SEBAGAI VARIABEL MODERASI PADA BANK UMUM SYARIAH DI INDONESIA - Muhammad Taufik (Universitas Islam Negeri Sumatera Utara, 2017)
The aim of this research was the influenced of financing to deposit ratio and capital adequacy ratio to return on asset that non performing financing as moderating variable on sharia commercial bank in Indonesia. This type of research is causality. The research sample using purposive sampling the sharia commercial bank which have annuall report containing the FDR, CAR, NPF, and ROA, it have sample 6 of sharia commercial bank begin in 2010 s.d 2015 resulted 36 observations. The analytical method used consisted of descriptive statistical analysis, classic assumption test, multiple linear regression test, hyphotesis tets, and test the moderating variables was interaction test. The results showed that all hypothesis is rejected. FDR negative effect and doesn`t significant on ROA. NPF does not moderate influence of FDR to ROA. CAR negative effect and doesn`t significant on ROA. NPF does not moderate influence of CAR to ROA. The results of this research have relevance to the data in the introduction section which describing condition of Islamic Banking.